Program Kemitraan Sekolah: Pemberdayaan Anak Usia Prasekolah Berbasis Terapi Komplementer Holtikultura - Candra Saputra; Umi Kalsum; Deswinda Deswinda; Arfina Arfina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Complementary horticultural therapy has the potential to improve gross motor skills in children. This therapy also provides hands-on experience and trains children's gross motor movements. Stimulated motor development in the form of movements of the hands, fingers, feet and limbs. The purpose is to carry out community service regarding the Implementation of Holticultural Complementary Therapy for Preschool Age Children at Nurul Ikhsan Integrated PAUD. The implementation method is carried out using Guided Training, FGD and Role Play techniques. The implementation of this community service activity was carried out for 2 days directly. The number of PAUD students involved in the activity was 32 people. Community Service Activities are carried out through 3 stages consisting of the preparation stage, implementation stage and evaluation stage. The results of community service activities show that the implementation of community service activities are carried out properly according to the plan. Evaluation of the results of the average value in the group given complementary horticultural therapy, namely pre-test 8.38 and post-test 11.06 and the average value in the group not given complementary horticultural therapy, namely pre-test 8.94 and post-test 9.06. These results can be concluded that there is an increase in gross motor skills in children.